2016
DOI: 10.3892/ol.2016.4892
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive pattern of let-7 family microRNAs in aggressive carcinoma of the oral tongue in young patients

Abstract: Oral cavity squamous cell carcinoma may be more aggressive at presentation and recurrence in young patients compared with older patients. Dysregulation of microRNAs (miRNAs or miRs) has been associated with the development and prognosis of oral cavity cancer. The present study investigated miRNA expression in carcinoma of the oral tongue in young patients. miRNA expression profiles were evaluated in formalin-fixed, paraffin-embedded samples of tumor and normal mucosa from 12 patients aged <30 years old with sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 62 publications
2
26
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are small non‐coding RNA molecules that induce post‐transcriptional gene silencing. Hilly et al revealed an up‐regulation of let‐7 family miRNAs, let‐7f‐5p, miR‐30b‐5p, and let‐7e‐5p in TSCC of young patients (≤30 years) compared to normal tissue. Additionally, up‐regulation of let‐7c, miR‐130a‐3p, miR‐361‐5p, miR‐99a‐5p, miR‐29c‐3p was found, and let‐7d‐5p was associated with more aggressive tumors.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
See 2 more Smart Citations
“…MicroRNAs (miRNAs) are small non‐coding RNA molecules that induce post‐transcriptional gene silencing. Hilly et al revealed an up‐regulation of let‐7 family miRNAs, let‐7f‐5p, miR‐30b‐5p, and let‐7e‐5p in TSCC of young patients (≤30 years) compared to normal tissue. Additionally, up‐regulation of let‐7c, miR‐130a‐3p, miR‐361‐5p, miR‐99a‐5p, miR‐29c‐3p was found, and let‐7d‐5p was associated with more aggressive tumors.…”
Section: Epigenetic Alterationsmentioning
confidence: 99%
“…The variability observed in the incidence of OSCC in young patients is partly explained by the arbitrary use of different cut‐off values to determine age groups, making difficult comparison of results obtained by different authors. Although most studies use ages ranging from 30 to 50 years, the majority considers young patients as those aged below 40 . In this group of patients, the oral tongue is the most affected site (41.1%‐61.3%) and there still is a male predilection, with a male:female ratio of 1.6:1 to 2.6:1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Let‐7a overexpression significantly inhibited the stemness signature and the chemoresistant abilities of HNSCC‐ALDH1 + cells . Moreover, one of the recent studies has indicated that there were higher levels of let‐7c and let‐7d‐5p in aggressive tongue tumors …”
Section: Introductionmentioning
confidence: 98%
“…15 Moreover, one of the recent studies has indicated that there were higher levels of let-7c and let-7d-5p in aggressive tongue tumors. 16 Accordingly, we sought to investigate the significance of let-7c in cancer stemness as other let-7 members play key roles in oral malignancy. First, we examined the expression of let-7c in normal, tumor, and metastasis tissues and showed the survival rate of patients in accordance with high or low expression of let-7c.…”
mentioning
confidence: 99%